PERUBAHAN SIKAP MURID MI PADA ERA PANDEMI DI MI MAMBA’UL HUDA NGABAR SIMAN PONOROGO: PERUBAHAN SIKAP MURID MI PADA ERA PANDEMI DI MI MAMBA’UL HUDA NGABAR SIMAN PONOROGO - Robbi, Ilham (Islamic Elementary School (IES), 2021)
Students of Madrasah Ibtidayyah (Mi) are students who take education at the level of elementary school but have significant differences in the context of their teaching so that they can achieve the goals of each educational institution. In this era, Indonesian people, especially those in Islamic boarding schools, prefer their children to take education at madrasah ibtidayyah with activities based on Islam but at this time there are many changes - changes in Mi students who deviate slightly from madrasah ibtidayyah education in the era of the Covid pandemic - 19. This study aims to find out the changes in Mi students in the Covid-19 Pandemic Era by using observation and interviews with resource persons who are also class teachers at Madrasah Ibtidaiyah. In an interview with one of the resource persons at Madrasah Ibtidayyah, it can be seen the changes that occur in Mi students with many problems in the child and bad relationships, but also from the family aspect who does not know the personality and nature of his child. However, there are solutions provided by resource persons to overcome the problems of change that exist in students so that they can be used as effective solutions for madrasah Ibtidaiyah teachers so that later the objectives of the learning can run smoothly.